1992
DOI: 10.1007/bf01437398
|View full text |Cite
|
Sign up to set email alerts
|

Resonantly enhanced two-photon excitation of sodium atoms in a heat pipe

Abstract: Abstract.We report the results of a study of two-color laser excitation, o91 + 092, in dense sodium vapor where o91 was tuned in the vicinity of the 3 P fine structure doublet and o92 was tuned to higher n I states. Resonant excitation by o92 of higher ns and nd states from one member of the 3P doublet when o91 is tuned near the other is attributed to collisional excitation transfer. Anomalous dipole forbidden p-p transitions are observed when 0) 2 is tuned to high nP states (> 20) and are believed to be DC e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…To explain how these weak peaks emerge through the excitation scheme (b) that we have used, let us consider the one photon transition from the second intermediate 5s6s 3 S 1 : dipole transitions to the 3 S 1 and to the 3 D 3 levels are forbidden, corresponding to a change of = 0 and = 2, respectively. Nevertheless, such dipole forbidden transitions have also been observed by other authors who used thermionic detectors and have been explained by -mixing processes, which are due either to collisions of the excited atom with neutral atomic perturbers in the oven (Burkhardt et al 1986, Zhang and Lu 1987, Wu et al 1990 or by the local Stark effect (Zhang et al 1992) induced by the bias voltage of the thermionic detector. In our experiment, either process could mix some p character into the wavefunctions of the 3 S 1 and 3 D 3 states: this part would then be excited from the 5s6s 3 S 1 intermediate by the third dipole transition.…”
Section: Snp Spectramentioning
confidence: 74%
“…To explain how these weak peaks emerge through the excitation scheme (b) that we have used, let us consider the one photon transition from the second intermediate 5s6s 3 S 1 : dipole transitions to the 3 S 1 and to the 3 D 3 levels are forbidden, corresponding to a change of = 0 and = 2, respectively. Nevertheless, such dipole forbidden transitions have also been observed by other authors who used thermionic detectors and have been explained by -mixing processes, which are due either to collisions of the excited atom with neutral atomic perturbers in the oven (Burkhardt et al 1986, Zhang and Lu 1987, Wu et al 1990 or by the local Stark effect (Zhang et al 1992) induced by the bias voltage of the thermionic detector. In our experiment, either process could mix some p character into the wavefunctions of the 3 S 1 and 3 D 3 states: this part would then be excited from the 5s6s 3 S 1 intermediate by the third dipole transition.…”
Section: Snp Spectramentioning
confidence: 74%
“…The parity-forbidden transitions have been reported in the spectra of alkalis and alkaline earths (Zhang and Lu 1987, Wu et al 1990, Gallagher 1994, Zia and Baig 2004. Burkhardt et al (1986) and Zhang et al (1992) observed the 3p → np parityforbidden transitions in sodium, and it was inferred that these transitions appear due to l-mixing collisions in the presence of the exciting laser. In magnesium and barium, the emergence of the parity-forbidden transitions was also characterized due to collisional l-mixing.…”
Section: Resultsmentioning
confidence: 96%
“…The appearance of these collisional-induced two-photon forbidden transitions are attributed to the formation of dimer excimer and were treated by the l-mixing model and perturbation theory. Zhang et al (1992) described the observation of dipole forbidden p-p transitions of sodium atoms in a heat pipe and explained their appearance due to the DC field which mixed the P state with the D states. Under our experimental conditions, we are limited in the range of variation of the discharge parameters, namely pressure and voltage.…”
Section: Resultsmentioning
confidence: 99%